Morphological aspects of buffaloes (Bubalus bubalis) umbilical cord - Ferreira,Guilherme J. (2009)
Buffalo is an important livestock resource, with a great participation in agricultural systems, providing milk, meat, and work power. Umbilical cord is responsible for maternal-fetal nutrients exchange during pregnancy, and its alterations can compromise the fetal development. We investigated ten pregnant uteruses collected from cross-bread buffaloes in different stages of gestation. Pregnancy and fetal age was determined by measuring the apex sacral length and development period was calculated by previously published formula. Umbilical cords were measured for length determination. Umbilical cord vascular net and anastomosis were observed by injection of Neoprene latex. Histological sections of the umbilical cord were studied after stain with HE, picrossirius, toluidine blue, orceine, and PAS reaction. Buffaloes' umbilical cord was formed by two central arteries, an allantois duct and two peripheral veins. The artery wall was composed by large quantity of collagen, elastic fibers, fibroblasts and large number of vasa vasorum. The allantois duct was located between the arteries and presented a great number of small nourishing vessels. Small nourishing vessels should be carefully considered to avoid to be mistaken to the arterials and veins vasa vasorum. Medium length of umbilical cord from buffalos was 11.8cm (minimum of 6.8cm and maximum of 17.4cm).